TAMI-31. GLIOBLASTOMA GENETIC DRIVERS DICTATE THE FUNCTION OF TUMOR-ASSOCIATED MACROPHAGES/MICROGLIA AND RESPONSES TO CSF1R INHIBITION. (12th November 2021) - Rao, Rohit; Han, Rong; Ogurek, Sean; Wu, Lai Man; Zhang, Liguo; Hu, Jian; Garrett, Matthew; Phoenix, Tim; Waggoner, Stephen N; Lu, Qing Richard
Abstract: Tumor-associated macrophages/microglia (TAMs) are prominent microenvironment components in human glioblastoma (GBM) that are potential targets for anti-tumor therapy. However, TAM depletion by CSF1R inhibition showed mixed results in clinical trials. We hypothesized that GBM subtype-specific tumor microenvironment convey distinct sensitivities to TAM targeting. We generated syngeneic PDGFB-driven and RAS-driven GBM models that resemble proneural-like and mesenchymal-like gliomas, and determined the effect of TAM targeting by CSF1R inhibitor PLX3397 on glioma growth and progression. We also investigated the co-targeting of TAMs and angiogenesis on PLX3397-resistant RAS-driven GBM. Using single-cell transcriptomic profiling, we further explored differences in tumor microenvironment compositions and functions between the proneural-like and mesenchymal-like glioma models. We found that the growth of PDGFB-driven tumors was markedly inhibited by PLX3397. In contrast, depletion of TAMs at the early phase accelerated RAS-driven tumor growth and had no effects on other proneural and mesenchymal human GBM models. In addition, PLX3397-resistant RAS-driven tumors did not respond to PI3K signaling inhibition. Single-cell transcriptomic profiling revealed that PDGFB-driven gliomas induced expansion and activation of pro-tumor microglia, whereas mesenchymal RAS-driven gliomas elicited TAMs enriched in pro-inflammatory and angiogenic signaling. Co-targeting of TAMs and angiogenesis decreased cell proliferation and tumor mass in RAS-driven gliomas. Our work identifies functionally distinct TAM subpopulations in the growth of different glioma subtypes. Notably, we uncover a potential responsiveness of resistant mesenchymal-like gliomas to combined anti-angiogenic therapy and CSF1R inhibition. These data highlight the importance of microenvironment landscape characterization to optimally stratify glioma patients for TAM-targeted therapy.